Pengaruh Intellectual Capital dan Struktur Modal terhadap Nilai Perusahaan - Holly, Anthony; Jao, Robert; Mardiana, Ana; Kusuma, Wilson (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The objective of this research is to analyze the influence of intellectual capital and capital structure on firm value. This study utilizes Signalling Theory and Trade-off Theory to explain the interrelationships between the variables. The population for this study comprises manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022. The sampling method used is purposive sampling, resulting in a sample of 28 companies with a total of 112 observations. Multiple regression analysis is employed to analyze the data, and hypothesis testing is conducted using the partial test (t-test). The results of this study indicate that intellectual capital and capital structure have a positive and significant effect on firm value. The findings also reveal that the enhancement of each factor significantly increases the firm value of manufacturing companies in Indonesia during the 2019-2022 period.